Topical Zhiyang Pingfu Liquid for Moderate to Severe Skin Rash Associated With EGFRIs: A double-blinded randomized controlled trial. (November 2022) - Zhang, Jingyi; Lu, Xingyu; Zhang, Xu; Tan, Kexin; Li, Jia; Cui, Huijuan
Background: Skin rash is the most common adverse effect associated with epidermal growth factor receptor inhibitors (EGFRIs). The study has observed the efficacy and safety of Zhiyang Pingfu Liquid in the treatment of EGFRIs-related moderate and severe rash. Methods: Patients suffering from EGFRIs-related moderate to severe rash were enrolled and then randomly divided into the treatment group and the control group, receiving Zhiyang Pingfu Liquid and placebo liquid respectively combined with minocycline and methylprednisolone recommended by guideline for 14 days. Changes in rash grades were observed, as well as the dosage of minocycline. Blood routine examination and liver and kidney function were evaluated to observe the safety of Zhiyang Pingfu Liquid. The total response of rash included complete response (CR) and partial response (PR). And the effective rate of rash was the percentage of CR and PR in the total cases. Results: A total of 54 out of 58 patients finished the study with 27 patients in each group. The effective rates of rash among the treatment group and the control group were 81.48% and 55.56% after 14 days treatment ( P  = .040). The treatment group had a lower dosage of minocycline compared with the control group. The median total dose of oral minocycline administration was 1000 mg in the treatment group and 1400 mg in the control group. Conclusion: Zhiyang Pingfu Liquid can effectively improve the moderate and severe EGFRIs-induced rash, and reduce the use of minocycline, as well as the side reactions brought by minocycline. However, larger randomized controlled trials are needed to verify these findings. Clinical Trial Registration: The trial was registered on the Chinese Clinical Trial Registry, the registration number is ChiCTR1800017053.